P-56 Establishing a research programme in an independent hospice. (19th November 2022) - Taylor, Paul; Kyeremateng, Sam; Lenton, Jo
Abstract : Background: Integrating research into the work of a hospice 'enables good quality care to be provided, described, evaluated and shared' (Hospice UK. Research and outcomes. [Internet]). Independent hospices act outside usual NHS research processes but remain subject to HRA stipulations (Health Research Authority, 2018). We report the establishment of a research programme in an independent hospice. Aims: To describe the process of developing and integrating a research programme in an independent hospice in the North of England. Methods: Over a five-year period, the hospice appointed a research lead, developed a research strategy, formed a research committee with board representation and established a governance process which reflects HRA requirements. Alongside these processes, the research lead captured existing research activity and outputs in a register, formed relationships with local and regional academic units, engaged with external studies and obtained funding for stand-alone projects. Results: Since beginning this programme, the hospice has a portfolio of research including 16 external studies we have supported as a recruitment site, ranging from small staff surveys/interviews to studies of patients/service users. We have also developed and led three studies, whilst the research lead has been a co-applicant on a further two. Hospice staff have published 11 papers in peer-reviewed journals and have generated 14 other outputs including dissertations, posters and oral presentations. The research lead is an active member of a University research group. Looking to future ambitions, we are planning on hosting a conference and are developing a 'flagship' project for submission to NIHR. Conclusion: The integration of research into hospice culture requires engagement at all levels of the organisation. Capturing existing activity, engaging with external research projects, forming relationships with academic centres and establishing governance procedures are important first steps. These processes form the foundation for an independent hospice to generate research and source external funding.